The Language Loyalty of Bilingual People in Boarding School Environment - Kartini, Ari; Sahidin, Didin (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
The study was carried out to investigate the language loyalty of bilingual people in Boarding School environment. The aims of the study were to describe the languages used by bilingual people in Boarding School environment, to identify the intensity level of language use and to explain the language loyalty of bilingual people. The study used analytical description of Qualitative methods. Questionnaire and Observation used to gather the data. To analyse the data, the researcher used sociolinguictic and descriptive approach. The study was conducted to 50 bilingual people based on gender, age, and profession. The result of the study suggested that 1) The languages used by bilingual people were Sundanese, Indonesian, English, and Arabic; 2) The high intensity level of language use was Indonesian, the second was Arabic, the third was Sundanese, the fourth was English; and 3) The loyalty of Sundanese use as a mother tongue was lower than other languages [Indonesia, Arabic, English]. The factors that contributed to the language loyalty of bilingual people were job demands that required to use Indonesian and Arabic, less confidence in using Sundanese correctly including the speech level [undak-usuk], and their existence in boarding school environment.